Lumpy skin disease is expanding its geographic range: A challenge for Asian livestock management and food security. (January 2022) - Azeem, Shahan; Sharma, Banshi; Shabir, Shafqat; Akbar, Haroon; Venter, Estelle
Abstract: In recent years, lumpy skin disease virus has extended its geographical range outside of endemic sub-Saharan countries to the Middle East and Asia indicating transboundary spread. Recently, lumpy skin disease (LSD) outbreaks have been reported in Asian countries such as Bangladesh, India, China, Nepal, Bhutan, Vietnam, Myanmar, Sri Lanka, Thailand, Malaysia, Laos and for the first time and represent a cause of serious concern for their livestock and dairy industries. This report summarizes information on the recent outbreaks of LSD in southern Asia and emphasizes the threat it poses to neighbouring countries. Various strategies and actions needed to control outbreaks of this emerging disease in Asia are also suggested.